Experiments with radioactive target samples at FRANZ. Issue 1 (January 2016) - Sonnabend, K; Altstadt, S; Beinrucker, C; Berger, M; Endres, A; Fiebiger, S; Gerbig, J; Glorius, J; Göbel, K; Heftrich, T; Hinrichs, O; Koloczek, A; et al.
Abstract: The FRANZ facility is currently under construction at Goethe Universität Frankfurt a.M., Germany. It is designed to produce the world's highest neutron intensities in the astrophysically relevant energy range between 10 keV and 1 MeV and consists of a high-intensity proton linac providing energies close to the threshold of the 7 Li(p, n) reaction at Ep = 1880 keV. The high intensities of both the proton and the neutron beam allow the investigation of reactions of unstable target isotopes since the needed amount of target material is significantly reduced. We will present two examplary reactions relevant for the s process and the nucleosynthesis of p nuclei, respectively.